Mass education materials published in the early period of People's Republic of China, 1949-1952 - Hunter, Edward, 1902- (1949)
These are the picture books and monographs published in Shanghai, Beijing, etc. during 1949-1952 about Chinese (most), Korean, and Russian heroes. They are not published by government agencies. Some include English translation.